A world survey of secular-religious competition: state religious policy from 1990 to 2014 - Fox, Jonathan (Religion, state & society, 2019)
This study argues that the competition between secular and religious actors significantly influences State religion policy (SRP) (the secular-religious competition perspective). I examine this proposition using the Religion and State Round 3 (RAS3) dataset which measures 117 types of SRP between 1990 and 2014 in 183 countries and territories. The results show that while SRP is overall becoming more common, only 3.7% of countries made no changes in their SRP and 69.5% of countries both (a) added or intensified at least one SRP and (b) dropped or decreased the intensity of at least one SRP. This finding remains consistent when looking at each of the 117 types of SRP independently, as well as when controlling for the country's majority religion and world region. These results are consistent with the secular-religious competition perspective.